The Quality of Rambak Cracker from Rabbit Skin (Water Content and Swelling Power) using The Different Technique of Fur Picking (Faculty of Animal Science Universitas Brawijaya, 2011)
This objective of this researchwas to compare the different technique of fur picking (liming and boiling) inthe quality rambak cracker from rabbit skin on water content and swelling power.Materials of this research were 20 drying rabbit skin 5 â€“ 6 months old. The tTest was using to compare the different technique of fur picking. Theindependent variables of this research were water content and swelling power onrambak cracker from rabbit skin. The result showed that the different techniqueof fur picking had highly significant effect (P<0.01) on water content and Â expanding rate. The best result was limingtechnique of fur picking. It had the following properties: Water content of 1.5922% and expending rate of 855.3798 %. The conclusion showed that the use limingof 4% produced high quality of rambak cracker from rabbit skin or anotheranimal skin (cow, buffalo, chicken or fish).Â Keywords: rambak cracker, rabbit skin, water content,expanding rate